Pharmacological effects and phytochemical profile of methanolic Odontosoria biflora (Kaulf.) C.Chr. [Lindsaeaceae] extract in Caenorhabditis elegans models of Parkinson’s disease - Hamel Darbandi, Meysam; Dalmacio, Leslie Michelle M.; Angeles, Jose Ma M. (Frontiers in Pharmacology, 2026)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by progressive dopaminergic neuronal loss, with oxidative stress and inflammation as key contributors to its pathogenesis. Odontosoria biflora (Kaulf.) C.Chr. [Lindsaeaceae], an endemic fern from Batanes Island, Philippines, is traditionally consumed as “tubho tea” and culturally associated with longevity. This study evaluated the pharmacological potential of O. biflora extract (OBE) in Caenorhabditis elegans models of PD. Leaves and stems were sequentially extracted using hexane (HOBE), ethyl acetate (EOBE), methanol (MOBE), and aqueous (AOBE) solvents. C. elegans N2, UA57, and NL5901 strains were cultured under standard conditions, and sublethal toxicity screening was conducted. The initial assay determined the effects of the four OBEs on dopaminergic neuronal loss in transgenic C. elegans, identifying MOBE as the most pronounced extract. MOBE was subsequently evaluated for α-synuclein aggregation, lifespan, mechanosensation, and locomotion. Antioxidant capacity was assessed using DPPH, ABTS, and FRAP assays as analytical tools, total phenolic content was determined, and phytochemical analysis was performed using high-resolution ultraperformance liquid chromatography coupled with electrospray ionization/quadrupole time-of-flight mass spectrometry. MOBE significantly reduced dopaminergic neuronal loss, decreased α-synuclein aggregation, extended lifespan, and improved mechanosensation and locomotion in transgenic Caenorhabditis elegans compared with both the negative and positive controls. Antioxidant assays demonstrated strong radical-scavenging activity consistent with its phenolic content (22.3 mg gallic acid equivalents [GAE]/g), and multiple metabolites were identified, including 1,4-dihydroxyanthraquinone, flavonoid 8-C glycosides, 2-O-rhamnosylvitexin, khellin, isovitexin, apigenin-8-C glucoside, benzoic acid, and pterosin G. Taken together, these findings suggest that MOBE exhibits pharmacological potential in C. elegans PD models and warrants further investigation in mammalian systems.